Knowledge and practices on prevention of complications of diabetes, among diabetic patients at a provincial general hospital and the facilities available - Perera, W.L.S.P (My University, 2006)
A cross sectional descriptive study with the objective of re-searching into the knowledge and practices on the prevention of complications of DM among diabetic patients attending the medical clinics and the services that were provided to them. A total of 385 diagnosed diabetic patients were interviewed using a questionnaire that was pretested. In addition, a checklist was utilized to collect information on the facilities that were available at the hospital. The respondents' knowledge on basic facts regarding blood sugar control showed mixed results. The knowledge on the increased risks for foot ulceration and amputation was almost universal but knowledge on the other chronic complications was unsatisfactory. The respondents' awareness of the risk factors for the development of complications was far from satisfactory. It was seen that the health care delivered was below the level expected from a Provincial General Hospital. Important aspects of patient education recommended by the authorities, was not provided. Time has come for the health care providers to reorganize the health services and improve the quality of care delivered to the diabetics, maximally using the existing resources. All the health institutions should have a clear policy on the management of the diabetics, adopting the national guidelines. These policies and guidelines must be implemented by improving the awareness of its staff time and again in addition to adequate supervision. In addition, a referral system, utilizing all government health institutions in the district makes a lot of sense in improving the delivery of health care.